Socio-economic development in India and five decades of planning - Shamshad, Ahmad (2004)
The economic development is not only hampered but also rendered fruitless in absence of social development. Amidst an unprecedented rate of economic growth, social improvements are found to be lagging. The distortions of development call for a halt now, if the society is to be saved from further degeneration. An accelerated place of socio-economic development in these depressing days perhaps holds of flicker of hope. The process of socio-economic development in India is analysed in the present article in the context of overall development during the last five decades of post-independence period. - Reproduced.
Keywords: Economic planning - India; Economic and social development - India; Economic and social development